Advances in Transportation Geotechnics and Materials for Sustainable Infrastructure 2014
DOI: 10.1061/9780784478509.007
|View full text |Cite
|
Sign up to set email alerts
|

Some Recent Developments in the Determination of the Atterberg Limits

Abstract: ABSTRACT:The Atterberg Limits are the most common tests specified by practicing geotechnical and pavement engineers the world over.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Given its apparent limitations, various attempts have been made to develop alternative testing approaches to the standard hand-rolling PL RT method, targeting higher degrees of repeatability and reproducibility. Most suggestions in this context are essentially strengthbased methods, executed using FC or reverse-extrusion devices, which mainly work on the premise of associating the PL RT with a set value of undrained shear strength (a more detailed review of these methods is given in O'Kelly et al [34], Vardanega and Haigh [45] and O'Kelly [46,47]). However, several studies have demonstrated that when considering a range of different fine-grained soils, the PL RT (onset of brittleness) does not correspond to a fixed value of undrained shear strength [22,34,36,37,[48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Given its apparent limitations, various attempts have been made to develop alternative testing approaches to the standard hand-rolling PL RT method, targeting higher degrees of repeatability and reproducibility. Most suggestions in this context are essentially strengthbased methods, executed using FC or reverse-extrusion devices, which mainly work on the premise of associating the PL RT with a set value of undrained shear strength (a more detailed review of these methods is given in O'Kelly et al [34], Vardanega and Haigh [45] and O'Kelly [46,47]). However, several studies have demonstrated that when considering a range of different fine-grained soils, the PL RT (onset of brittleness) does not correspond to a fixed value of undrained shear strength [22,34,36,37,[48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Skempton, 1944Skempton, , 1954Skempton, , 1957Karlsson & Viberg, 1967;Stroud, 1974;Wroth, 1979;Carrier & Beckman, 1984;Larsson et al, 1987;Nakase et al, 1988;Wood, 1990;Tripathy & Mishra, 2011;Sørensen & Okkels, 2013;Farias & Llano-Serna, 2016). The liquidity index (I L ) parameter is used in codified design approaches for deep foundations in Russia (see Vardanega et al, 2012;Vardanega & Haigh, 2014a;Kolodiy et al, 2015) and in geomorphological research to characterise soils at a more regional level (e.g. Amir-Faryar et al, 2015;Stanchi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%